Examining the Correlates of Prison Misconduct among Elderly Inmates. Issue 3 (2nd July 2016) - Hilinski-Rosick, Carly M.; Freiburger, Tina L.
ABSTRACT: There is a large body of research examining prison misconduct and the driving forces behind inmates who engage in this behavior. The deprivation and importation models are the most common explanations for inmate misconduct. Research has suggested that deprivation and importation factors affect prison behavior and that the significance of these factors often varies across groups. The current research attempts to fill a gap in the literature examining the differences between inmates who were younger, middle age, and older in misconduct using data from inmates incarcerated in West Virginia during 2010. This study adds to the limited body of research specifically assessing the differences in prison misconduct across different age groups; policy implications also will be offered.